Detection and quantification of Bacillus cereus and Bacillus thuringiensis from cooked rice and burger employing most probable number-polymerase chain reaction (MPN-PCR) method - Sandra, Afriani (2012)
The aim of this study was to determine the prevalence and number of Bacillus cereus and Bacillus thuringiensis in cooked rice and burgers in Serdang, Selangor, Malaysia. A combination of Most Probable Number Polymerase Chain Reaction (MPN-PCR) method was applied to detect the presence of total B. cereus and B. thuringiensis harboring gyrB genes. The biosafety of B. cereus were assessed by antibiotic resistance test of the isolates from both cooked rice and burger samples. A kitchen simulation study was conducted to investigate germination of B. cereus with the storage condition similar to domestic kitchens (ambient temperature). Estimation of the risk of illness and risk rating from consumption of cooked rice and burger were investigated using semi-quantitative Risk Ranger spreadsheet tool. The prevalence of B. cereus group was relatively high in cooked rice with ranged of 50% to 100% and burger 26.6% to 46.2%. The prevalence of B. thuringiensis was 10% to 35.2% for cooked rice and 10.8% to 33.9% for burger. However,none of raw rice samples were positive for B. thuringiensis but all samples were positive for B.cereus. The study was extended to investigate the level of contamination in cooked rice. A total comprised of 115 samples of nasi lemak (n=54), nasi briyani (n=20), nasi ayam (n=20) and nasi putih (n=21) were collected from mention the places. Nasi ayam was found to have higher prevalence (100%) of B. cereus compared to nasi putih (76.2%) and nasi lemak (70.4%), while nasi briyani have lowest prevalence (50%). Only 10% of nasi putih and nasi ayam, 30% of nasi briyani and 35.2% of nasi lemak samples were found to harbor B. thuringiensis. Furthermore, 197 burger samples were analyzed. Fish burgers had higher contamination level (46.2%) compared to beef burgers (41.5%) and chicken burgers (26.6%) for B. cereus. Prevalence of fish burgers had lowest contamination level for B. thuringiensis (10.8%) compared to chicken burgers (13.9%) or beef burgers (33.9%). A total of 92 B. cereus isolates were recovered by plating method and confirmed by PCR. Antibiotic resistance profiling indicated that multi-resistance to B. cereus might be wide-spread in the study area. The isolates showed multi-resistance to 8 antibiotics tested, with 98.9% resistance to ampicillin and mostly susceptible to norfloxacin (1.1% resistance). High Multiple Antibiotic Resistance (MAR) indices were detected in this study (ranging from 0 to 0.63) with more than 54.3% of the isolates had a MAR index value of 0.36 and 42.4% showed MAR index of 0.25. At domestic kitchen level, simulation on the germination of B. cereus by storing cooked rice was carried out. In this study the simulation was designed to imitate real events in domestic kitchens as much as possible to give a realistic quantitative data on how B. cereus spores can germinate while storing at ambient temperature. The four storing times (0, 6, 12, and 18 h) were applied in the simulation study. Tap water was used to wash raw rice before cooking procedures and dishwater from washing rice was investigated to test if washing step can reduce contamination of B. cereus in raw rice. In this study, both naturally and artificially contaminated raw rice were used. The mean concentration of B.cereus in the samples after storage for 18 h was 2.8 MPN/g both for washing and without washing raw rice. Number of B. cereus ranged from 460 MPN/g up to 1100 MPN/g values. It was found that rinsing can greatly reduce the number of B. cereus in raw rice samples (up to 0.88 log reduction). The potential of cooked rice and burgers as a B. cereus transmitter was demonstrated by semi-quantitative Risk Ranger spreadsheet. Based on the assumptions used in the risk ranger, nasi putih had the highest predicted cause of illness. It was assumed that nasi putih is a staple food in Malaysia with average consumption of 2x/day. The risk ranking is 47 with predicted illnesses of 1800 per annum. Considering Malaysian population of 28.7 million, it is assumed that 75% of population consumes nasi putih. However, the risk estimate was predicted to be reduced when less people consuming the contaminated foods. In conclusion, the results suggested that cooked rice and burger act as a transmission route for B. cereus and thus pose a risk for consumers. Further studies on a bigger scale are recommended for a better understanding on the presence of B. cereus in cooked rice and burgers and the risks involved in consumption of such foods.